Compressive behavior of FRP externally wrapped R.C. column with buckling effects of longitudinal bars. (1st August 2018) - Campione, G.; Cannella, F.; Ferrotto, M.F.; Gianquinto, M.
Highlights: Compressive behavior of R.C. columns with square cross-sections externally wrapped with FRP. Buckling effects of the longitudinal bars. Reduction of the confinement pressure induced by the buckled compressed bars. Critical length and critical stress of compressed bars including interaction effects between concrete cover, stirrups and FRP wraps. Abstract: In this paper, a calculation model to simulate the compressive behavior of R.C. columns with square cross-sections externally wrapped with FRP, including buckling effects of the longitudinal bars and reduction of the confinement pressure induced by the buckled compressed bars, is presented and discussed. The model distinguishes the cases of corner and side bars, calculating the different critical lengths and the critical loads. The Teng et al. (2009) model was adopted to predict the compressive behavior of FRP-confined concrete, and the Dhakal and Maekawa (2002) model was taken into account to predict the compressive behavior of longitudinal bars. The critical length and critical stress of compressed bars including interaction effects between concrete cover, stirrups and FRP wraps were calculated, distinguishing between corner and side bars. Based on the model mentioned, analytical expressions were derived to calculate the critical strain at the onset of bar buckling and the minimum thickness of FRP to prevent instability of the compressed bars. Finally, a theoretical–experimental comparison was made to validate the model.